ADDRESSING THE IMPACTS OF TEXTILE INDUSTRIES ON ENVIRONMENT AND SOCIO- ECONOMIC CONDITION OF BANK TOWN AND BARAIGRAM AREA: A MANAGEMENT PERSPECTIVE - Alam, S.M. Mahbub; Hussain, Md. Muaz; Islam Himel, Aminul; Hoque, Md. Erfanul; Hossain, Md. Maruf (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Textile industry is a well-established industrial sector in Bangladesh and ranked top in terms of export earnings. Because of its high value addition and huge growth and employment opportunities, textiles a thrust sector of the country. Textile industry of Bangladesh includes yarn and fabric manufacturing, dyeing and printing, making ready-made garment products and exporting them. A huge quantity of solid and liquid wastes is dumped out of the textile industries in Bank Town and Baraigram Area. The toxic effluents and solid waste of the textile industries contaminate soil, air and the water of the adjacent Karnatali river and leads to severe ailments such as eye diseases, skin irritations, kidney failure and gastrointestinal problems. Besides the ETP of these industries are not used properly. The industries in this area are adjacent to the locality. So, the government needs to be conscious about the externalities of the project. Because these unplanned industries could cause severe damages to agricultural land and species of Karnatali River. Not only the adverse environmental impact but also the socio-economic issues such as availability of inputs, skilled workers and markets, provision of adequate accommodation for the workers and standard of living condition. To make it fruitful, environment friendly, long according the detailed feasibility and EIA study of the project. There also needs address the probable risks of the project on the surrounding agricultural lands, river human health, surrounding environment and socio-economic condition of the people After addressing those problems necessary and fruitful initiatives the planning perspectives should have to be taken to make this contemporary policy fruitful for the environment, surrounding areas, people and finally for the economic structure of the country.